Access to justice through clinical legal education: a way forward for good governance and development (2015)
Access to justice is a fundamental right that ought to be universal, but a lack of effective access to justice is frequently identified as a major barrier to realising human rights. This relates especially to women. Nigerian women are not sufficiently protected by the legal system. Women in Africa, generally, and in Nigeria, in particular, face numerous barriers that hinder their access to legal services and assistance from legal institutions that are set up to redress wrongs. Under the Constitution of the Federal Republic of Nigeria 1999, it is the duty of government to ensure that all citizens have access to justice. Legal aid clinics have in the last decade developed alongside other governmental legal services. The article discusses the evolution of legal clinics in educational institutions and by non-governmental organisations in Nigeria and focuses in particular on how access to justice through the intervention of the Women’s Law Clinic, University of Ibadan, has impacted on governance and development